Analysis of the Relationship of Local Rice Cultivar (Oryza Sativa L.) in Bulungan District Based on Characteristics and Morphology - Taty Haryati Dewi; Marlan Usmani Putra; Tiara Aprilia (Information Technology and Science (ITScience), 2024)
Local rice originates from the Bulungan region of North Kalimantan. Generally, this rice plant is cultivated by the community and divided into two parts, namely mountain or field rice and paddy fields. Differences and similarities in morphological characters in rice cultivars can be distinguished through characterization. Morphological characterization needs to be done to identify specific characters that appear directly, especially characters related to the growth and development of rice plants that can increase the potential for rice yields. Morphological characterization analysis is used to determine the distance and kinship between rice cultivars. This study aims to determine the differences in morphological characters and kinship relationships between 6 local rice cultivars in several areas of Bulungan Regency, namely three types of rice originating from peso villages such as leto Yukon, amai sampan, and anak Leto, while three varieties are types of rice originating from Tanjung Selor. The research was conducted at the Green House of the Faculty of Agriculture, University of Kaltara. The research method used is a descriptive qualitative method, and the data was analyzed using SPSS pc 23.0 software with a scoring form that forms a cluster and produces a dendrogram. The results showed that several local rice cultivars have similarities in several morphological characteristics, such as plant age (HSS), plant height (cm), stem color, leaf blade color, leaf ear color, and leaf tongue color. The similarity coefficient formed is 1,000, and 2 groups (clusters) are formed with close kinship relationships.